Complete occlusion of the left main trunk coronary artery by a cardiac papillary fibroelastoma in a hemodynamically unstable patient. Issue 4 (April 2016) - Chiba, Nobutaka; Matsuzaki, Masakazu; Furuya, Shingo; Iida, Kiyoshi; Wakui, Shinji; Akiyama, Kenji; Kinoshita, Kosaku
Abstract: Papillary fibroelastomas are benign cardiac tumors with high embolic potential. The majority of cases of complete obstruction of the left main trunk (LMT) of the coronary artery are diagnosed via autopsy following sudden death; survival is rare in this setting. We present the case of a 60-year-old woman who underwent stent placement in the LMT three years prior to developing chest pain and cold sweats. On coronary arteriography, the catheter could not be advanced into the LMT due to resistance in the ostium. Insertion of the catheter was achieved after the resolution of resistance via catheterization of the LMT by means of an intra-aortic balloon pump drive system. The LMT was normal, and the patient's circulatory failure improved. The cause of the LMT embolism was a cardiac papillary fibroelastoma. Primary surgical excision is the recommended therapy for symptomatic cardiac papillary fibroelastoma. If the patient is hemodynamically stable, it may be possible to delay surgery. However, the patient in question developed cardiogenic shock secondary to two-vessel obstruction by the tumor. Therefore, even if the tumor had been removed using an intra-aortic balloon pump, the patient may not have survived until surgery. <Learning objective: Primary surgical excision is the recommended therapy for symptomatic cardiac papillary fibroelastoma. If the patient is hemodynamically stable, it may be possible to delay surgery. However, hemodynamically unstable patients may not survive until surgery. Therefore, emergent therapy is a useful stop-gap measure until surgery is feasible.>